Headache Characteristics in Children With Pseudotumor Cerebri Syndrome, Elevated Opening Pressure Without Papilledema, and Normal Opening Pressure: A Retrospective Cohort Study - Hamedani, Ali G. (Headache, 2018)
BACKGROUND. Certain headache characteristics and associated symptoms are commonly attributed to increased intracranial pressure, but they have not been systematically studied among children in the context of revised diagnostic criteria for pseudotumor cerebri syndrome (PTCS). METHODS. We performed a retrospective cohort study of patients treated for suspected or confirmed PTCS. Charts were reviewed for PTCS and headache diagnostic criteria and associated characteristics. Chi-squared or Fisher’s exact tests were used to compare the frequency of headache characteristics between groups. RESULTS. One hundred and twenty-seven individuals were identified: 61 had definite PTCS, 10 had probable PTCS, 31 had elevated opening pressure (OP) without papilledema, and 25 had normal OP without papilledema. Eleven children had no headache (6 with definite PTCS, 5 with probable PTCS). Headache pattern was episodic in 49% (95% CI: 34–64%) of those with definite PTCS, 18% (95% CI 6–37%) of those with elevated OP without papilledema, and 16% (5–36%) of those with normal OP without papilledema. Headache location was more likely to involve the head along with neck or shoulders in those with definite PTCS compared with elevated OP without papilledema (OR = 7.2, 95% CI: 1.9–27.6) and normal OP (OR = 4.5, 95% CI: 1.3–15.6) groups. DISCUSSION. While missing data and small cohort size are limitations, this study suggests that headache in PTCS is more likely to involve the head along with neck/shoulders, and that headache in PTCS may be episodic or constant. Headache is occasionally absent in PTCS.